IMPLEMENTASI MANAJEMEN ISI KURIKULUM KARAKTER ISLAMI DI MADRASAH IBTIDAIYAH MIFTAHUL ULUM PULAU MANDANGIN SAMPANG - Moh. Zainuddin Syarif; Burdatun Warida (re-JIEM (Research Journal of Islamic Education Management), 2022)
The implementation of load management of the curriculum is packed with Islamic programs which aim to develop the Islamic character of learners. By using case study method, it is known that the content of Islamic character curriculum content in MI Miftahul Ulum Mandangin Island is applied with the addition of curriculum charge in the development section self. On the charge MI Miftahul Ulum is implementing a religious program. In addition, MI Miftahul Ulum also built an Islamic culture. The process of content management of Islamic character curriculum is also developed here. In the implementation of this also got inhibiting factor and supporter. The changes in behaviors or outcomes of this implementation can be felt like the low violations committed by students, the religious behavior that follow and the realization of a thick Islamic culture.